1-Chloro-2-(4-phenylpiperazin-1-yl)ethanone - Yong-Ji Xu; Fei Jing (Acta Crystallographica Section E, 2009)
The title compound, C12H15ClN2O, is a piperazine derivative with the potential for use as a starting material for pharmaceutial and agrochemical applications. The structure is stabilized by C—H...O hydrogen bonds, C—H...π interactions and π–π stacking interactions [centroid–centroid distance = is 4.760 (2) Å].